2018
DOI: 10.13066/kspm.2018.13.3.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taping on a Home Program of Hip Abductor Exercise on Pain and Quadriceps Muscle Strength in Elderly Women with Knee Osteoarthritis

Abstract: PURPOSE: This study was conducted to determine the effects of taping on a home program of hip abductor exercise on pain and quadriceps muscle strength during knee joint osteoarthritis. METHODS: The subjects were 24 elderly women aged over 65 years with knee joint osteoarthritis. Twenty-four subjects were divided into two groups of 12. The intervention was conducted three times a week for six weeks. The control group underwent a home program of hip abductor exercise, while the experimental group underwent tapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…11,15,17 –20 Two studies used manual therapy, 10,18 and eight studies used exercise training in the treatment programs. 11,13,14,16,20 –23 Moreover, seven studies com-bined more than two types of physical therapies. 10,11,15,17 –20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,15,17 –20 Two studies used manual therapy, 10,18 and eight studies used exercise training in the treatment programs. 11,13,14,16,20 –23 Moreover, seven studies com-bined more than two types of physical therapies. 10,11,15,17 –20…”
Section: Resultsmentioning
confidence: 99%
“…In the 15 studies, the follow-up after initial treatments ranged from three days to 15 weeks. Subjective pain reduction score was measured in 14 of 15 studies: 12 studies used the visual analogue scale, 10 13,15 –20,23,24 and the remaining two studies used numeric pain rating scale. 14,22 A functional scale was used in 12 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 35 full text articles were evaluated in full texts according to the inclusion and exclusion criteria. Finally, 16 studies were included to perform the meta-analysis (Malgaonkar and Rizvi, 2014;Castrogiovanni et al, 2016;Dhanakotti et al, 2016;Sarallahi et al, 2016;Sedhom, 2016;Aydogdu et al, 2017;Saswadkar et al, 2017;Taheri et al, 2017;Tripathi and Hande, 2017;Bao et al, 2018;Choi, 2018;Günaydin and Bayrakci Tunay, 2020;Leon-Ballesteros et al, 2020;Varma and Purohit, 2020;Danazumi et al, 2021;Oguz et al, 2021). In the excluded articles, no exercise was performed on ten studies, two were cross-sectional studies, one was a comment study, two were self-control studies, two studies were not randomized, one study had no data and one study had only one group (details were shown in Supplementary File S3).…”
Section: Study Selectionmentioning
confidence: 99%
“…무릎 관절에서 흔하게 발생되는 질환에는 골관절염, 관절 주변부의 인대 손상, 점액낭염, 넙다리네갈래근의 염좌, 무릎 반월판 손상과 무릎넙다리통증증후군 등으 로 다양하다 (Choi, 2018;Jun and Park, 2015). 이 중에서 무릎넙다리통증증후군(patellofemoral pain syndrome; PFPS)은 대표적인 무릎관절 주변부의 증상으로서 요즈 음에는 관절염과 함께 스포츠 분야나 정형외과에서 가 장 흔한 증상이 되었다 (Coburn et al, 2018 (Dixit et al, 2007;Fredericson and Yoon, 2006).…”
Section: ⅰ 서 론unclassified